Learning Strategies in Speaking for Presentation Applied by EFL Students - Rahma Viranita; Ildi Kurniawan; Azhar Aziz Lubis (Journal of English Education and Teaching, 2023)
This research aims to find out the types of learning strategies in speaking for presentation applied by the fourth semester students’ of the English Education Study Program at the University of  Bengkulu. This research was descriptive quantitative research. The population of this research was the fourth-semester students of the English Education Study Program of the University of Bengkulu in the 2020-2021 academic year. The total sample of this research was 28 students. The data were collected by using a questionnaire. The questionnaire consisted of 18 items which 3 categories strategies (Cognitive strategy, Metacognitive strategy, and Social-affective strategy).  The questionnaire was adapted from (Liao & Chiang, 2004). This research used SPSS (Statistical Package for the Social Science) 16.0 program to get the types of learning strategies in speaking for presentation applied by the fourth semester students’. The results of this research showed the type of learning strategies applied applied by students, is cognitive strategy. The cognitive strategies with a weighted average 3.15. Then, the metacognitive strategies with a weighted average 3.09. The last, the social-effective strategies got weighted avarage 3.07. Similarly, it can be concluded  the types of learning strategies in speaking for presentation applied by the fourth semester students’ were Cognitive strategies.